TRANSLATION OF TERMINOLOGY: BRIDGING LANGUAGE GAPS IN SCIENTIFIC COMMUNICATION - Todjidinova Umida Uriboy qizi (Galaxy International Interdisciplinary Research Journal, 2024)
Importance of Translation: The introduction highlights the significance of clear and precise terminology in scientific communication. It emphasizes how language barriers hinder access to scientific literature and impede the sharing of research findings among researchers worldwide.